2002
DOI: 10.1046/j.0143-2885.2001.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three root canal sealers on the retentive strength of endodontic posts luted with a resin cement

Abstract: The chemical formulation of root canal sealers did not significantly affect the retention of endodontic posts luted with resin cement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
50
1
19

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 15 publications
12
50
1
19
Order By: Relevance
“…Despite these drawbacks, the use of natural teeth in the evaluation of post systems has been considered acceptable by investigators in this field (7). The group sample size was in agreement with that used in studies of a similar nature (8). The teeth were stored in a chlorhexidine/ distilled water solution to prevent bacterial overgrowth during periods of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these drawbacks, the use of natural teeth in the evaluation of post systems has been considered acceptable by investigators in this field (7). The group sample size was in agreement with that used in studies of a similar nature (8). The teeth were stored in a chlorhexidine/ distilled water solution to prevent bacterial overgrowth during periods of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is postulated that the adhesive procedures are favored when the dentin is free of previous contamination from eugenol-based endodontic sealers (7,9). This behavior is observed not only for eugenol-based sealers, but also to epoxy-resin and calcium hydroxidebased sealers, as used in this study (8,10,18). Moreover, the preparation of the post space after the setting period of the sealer reduces the possibility of apical infiltration due to improved apical sealing (19).…”
Section: Discussionmentioning
confidence: 79%
“…20,21 The other is that no decrease in the bond strength values of resin cements has been observed. 22,23 In addition, the effects of other endodontic sealers with various resin cement bond strength studies comparing these resin cements have provided contradictory results. [17][18][19] Demiryürek et al 12 concluded that either resin or eugenol-based sealers have no adverse effect on the bond strength of resin cement, but that calcium hydroxide-based sealers show results similar to those in a control group.…”
Section: Introductionmentioning
confidence: 99%